1997
DOI: 10.1074/jbc.272.26.16096
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine 140 of the γ-Aminobutyric Acid Transporter GAT-1 Plays a Critical Role in Neurotransmitter Recognition

Abstract: The gamma-aminobutyric acid (GABA) transporter GAT-1 is located in nerve terminals and catalyzes the electrogenic reuptake of the neurotransmitter with two sodium ions and one chloride. We now identify a single tyrosine residue that is critical for GABA recognition and transport. It is completely conserved throughout the superfamily, and even substitution to the other aromatic amino acids, phenylalanine (Y140F) and tryptophan (Y140W), results in completely inactive transporters. Electrophysiological characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
109
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 33 publications
7
109
0
Order By: Relevance
“…Both mutants are inactive in GABA-induced steady-state transport currents. It was concluded that Y140 may be involved in the ligand binding of the amino group of GABA and other neurotransmitters (Bismuth et al, 1997). Fleetrophysiological studies also indicate that the conserved residue W68 in the first putative TM I ofGATI may be involved in the binding of Na'' and/or CL' (Mager et al, 1996).…”
Section: Substrate Binding and Trans!ocationmentioning
confidence: 99%
“…Both mutants are inactive in GABA-induced steady-state transport currents. It was concluded that Y140 may be involved in the ligand binding of the amino group of GABA and other neurotransmitters (Bismuth et al, 1997). Fleetrophysiological studies also indicate that the conserved residue W68 in the first putative TM I ofGATI may be involved in the binding of Na'' and/or CL' (Mager et al, 1996).…”
Section: Substrate Binding and Trans!ocationmentioning
confidence: 99%
“…This tyrosine residue is conserved in all the family members, including the bacterial transporters (24). It has been suggested that the tyrosine may interact with a moiety common to all substrates of the family, namely the amino group (22).In this study we have modified Tyr 288 and the conserved Tyr 289 located in the TMIII of GLYT2a transporter. By using a glycine transport assay and the whole cell recording configuration of the patch-clamp technique, we have studied the functional effects of these point modifications.…”
mentioning
confidence: 99%
“…Previous work from related GABA (GAT-1) and serotonin (SERT) transporters point to a tyrosine residue and its surroundings in the third transmembrane domain (TMIII) as being critical in substrate binding (22,23). This tyrosine residue is conserved in all the family members, including the bacterial transporters (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although little is known about the three-dimensional structure of these transporters (16), site-directed mutagenesis approaches have permitted the identification of critical residues for the transport function in TMI, -III, and -IV (17)(18)(19)(20)(21)(22), which are candidates to contribute to the binding of substrates. In addition, conformationally active residues have been identified in several hydrophilic loops (23)(24)(25)(26)(27)(28)(29)(30), and it has been suggested that IL2-IL3-IL4 might be part of an intracellular "gating" domain, because a mutation of three residues in those loops of DAT seems to disrupt intramolecular interactions stabilizing the conformation able to bind extracellular substrate (31)(32)(33).…”
mentioning
confidence: 99%